ANALISIS VARIASI METODE PEMBELAJARAN BAHASA INDONESIA PADA MURID KELAS II SDN 121/I MUARA SINGOAN - Mega Afriani Sihite; Nuzul Rahmadani; Ryka Ayu Lestari; Khoirunnisa (STKIP Subang, 2026)
This study explores how teaching methods are actually practiced in Indonesian language learning in a second-grade classroom at SDN 121 Muara Singoan. A qualitative descriptive approach was employed through classroom observation and teacher interviews. The findings show that three methods are used: lecture, discussion, and assignment. However, their use is not equally distributed. The lecture method dominates classroom activities and is deliberately chosen by the teacher as an effective way to build students’ basic understanding. In lower-grade classrooms, students still require clear and structured explanations before engaging in more interactive activities. Despite its effectiveness at the initial stage, the extended use of lecture tends to create a one-way learning pattern. Students become more passive, and opportunities for interaction are limited. Discussion appears only in brief question-and-answer sessions, while assignments function mainly as reinforcement. This condition indicates that method variation exists, but its implementation has not yet fully supported active student participation. A more balanced combination of methods is needed to create a learning environment that not only delivers understanding but also encourages engagement.